Disturbance ecology and the problem of n = 1: A proposed framework for unifying disturbance ecology studies to address theory across multiple ecological systems. Issue 12 (21st August 2021) - Buma, Brian
Abstract: Disturbances are a key part of ecosystem dynamics at multiple scales. They can maintain ephemeral habitat, alter local and landscape biodiversity, drive carbon balance changes and trigger whole ecosystem regime shifts. Yet, there are few theories and only limited frameworks underlying disturbance ecology by which scientists and practitioners can anticipate the impacts of novel disturbances or changes in disturbance regimes. Much of the challenge in developing and testing theories lies in the diversity of ecosystems and disturbance processes and the general inability to (a) properly replicate studies and (b) compare results across disparate systems, from bacterial communities to boreal forests. General syntheses of disturbance processes have identified key aspects of disturbance impact and response—resource stock change, resource flux change, spatial dynamics and trait diversity—that should apply across systems. Yet, application and testing remain challenging due to a lack of a common set of metrics and baselines for comparisons across systems. Here, I propose a discipline‐wide effort to develop and publish standardized metrics (in addition to study‐specific data) such that the field as a whole can build and test general theory that works across ecological systems. Ten metrics spanning event type, location/design data and biotic composition comprise this suite of 'minimum descriptors' and are directly derived from current disturbance ecology theory. Several examples of cross‐system applicability, from bacterial studies to palaeoecological disturbances, are noted. These are example metrics, intended to open the conversation about the most appropriate and theory‐based lines of commonality across the field, and they may be further refined through cross‐disciplinary conversation. The result of standardizing metrics will be a coordinated dataset that allows for inter‐system testing of theory, meaning disturbance ecology studies can move past disparate, seemingly unique systems with little replication to integrated research. To phrase it in another way, disturbance ecology studies should be planned, in part, to contribute to future quantitative meta‐analyses. If done, we (as a community) will be much better prepared to address the challenges of emerging disturbances, novel ecosystems, and no‐analogue changes in disturbance regimes which are anticipated with climate change and increasing human pressures.